The Minimization of Torque Ripples of Segmental Type Switched Reluctance Motor by Particle Swarm Optimization - Terzioğlu, Hakan; Herdem, Saadetdin; BAL, Güngör (Prof. Dr. Ismail SARITAS, 2016)
In this study, we realized a controller design which can reduce torque ripple of 10/8 Switched Reluctance Motor (SRM). To perform the study, a Switched Reluctance Motor with 5 phase, U type segmental rotor was used. The control of the SRM was actualized by bipolar converter used H-bridge topology. The control signals of converter are obtained by control circuit designed by using dsPIC33EP512MU810. One of the reasons of the current ripples in the SRM is ON-OFF times in a period of the control signals. When the ripples of the current reduced, the ripples of torque of the SRM also reduced. Therefore, in this study, the ON-OFF times in a period of phase control signals were determined by an algorithm used particle swarm optimization. When SRM was controlled by this algorithm developed, the decreasing of its torque ripples was determined.